Applying The Principle of Insurance on The Credit Life Insurance in The Consumer Lending - Faizal Kurniawan; Prawitra Thalib; Hilda Yunita Sabrie (Rechtsidee, 2017)
The specific task of the commercial banks are as follows: the bank must distribute most of the credit for developing the activities of the cooperatives and entrepreneurs economically weak or small entrepreneurs, the public banking that provides credit in foreign currency required to distribute some the foreign currency credit to finance the activities of non-oil exports and required to perform an assessment of the fulfillment the terms of the feasibility of the debtor's business. In carrying out its functions, the bank must still run banking principles contained in the articles contained in the Banking Act. It is often in distribute the credit, the bank requires the third party, such as the insurance companies. The purpose of insurance companies is to minimize the risks that may be experienced by the bank as debtors failed to pay. The bank is very concerned with their insurance company. There are various types of loans that cannot be separated by the insurance, this study focuses on consumer credit in PT. Bank Jatim. In practice, especially consumer credit lending cannot be separated from the role of the insurance companies. But in operating the bussiness, the insurance companies should also continue to apply the principles of general insurance. The application of the insurance principle is intended that no aggrieved parties. Generally speaking, there will be a conflict of interest between the application of the principles of insurance carried by the insurance company as an insurer with the business aspect of the field of insurance and banking.